Analisis Pemahaman Konsep Matematika Kelas X AKL SMKS SEMESTA Depok pada Materi Logaritma - Putri Khairani; Ika Nur Bella Fitriyani; Yogi Arif Fathan (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
Concept mastery is the level of learning outcomes where students can explain or define lesson concepts using their own sentences or parts of them. This research approach uses a qualitative descriptive method. Qualitative research is about describing the meaning of data or phenomena that can be captured by researchers, by showing evidence. The meaning of this phenomenon depends a lot on the researcher's ability and sharpness in analyzing (Abdussamad, 2021: 30-31). The results obtained from this research come from documentation data. From the documentation data, 24 students will analyze the understanding of mathematical concepts in class X AKL SMKS SEMESTA, Depok. The results per category can be concluded that there are 15 respondents or 64% of students who have a high level of ability to understand mathematical concepts in logarithm material with high criteria, then there are 7 respondents or 29% of students who have a level of ability to understand mathematical concepts of logarithm material with medium criteria, and there are 2 respondents or 8% of students who have a low level of ability to understand mathematical concepts regarding logarithm material..